Mechanisms of naturally acquired immunity to P. falciparum and approaches to identify merozoite antigen targets. Issue 7 (16th November 2017) - Healer, Julie; Chiu, Chris Y.; Hansen, Diana S.
Abstract: Malaria is one the most serious infectious diseases with over 200 million clinical cases annually. Most cases of the severe disease are caused by Plasmodium falciparum . The blood stage of Plasmodium parasite is entirely responsible for malaria-associated pathology. The population most susceptible to severe malaria are children under the age of 5, with low levels of immunity. It is only after many years of repeated exposure that individuals living in endemic areas develop clinical immunity. This form of protection prevents clinical episodes by substantially reducing parasite burden. Naturally acquired immunity predominantly targets blood-stage parasites with antibody responses being the main mediators of protection. The targets of clinical immunity are the extracellular merozoite and the infected erythrocyte surface, with the extremely diverse PfEMP1 proteins the main target here. This observation provides a strong rationale that an effective anti-malaria vaccine targeting blood-stage parasites is achievable. Thus the identification of antigenic targets of naturally acquired immunity remains an important step towards the formulation of novel vaccine combinations before testing their efficacy in clinical trials. This review summarizes the main findings to date defining antigenic targets present on the extracellular merozoite associated with naturally acquired immunity to P. falciparum malaria.